Adolf Meyer correspondence - Meyer, Adolf, 1866-1950.
ALS (1936 July 4) from Meyer addressed to a Mr. Smith concerning a manuscript written by Smith.
Psychiatrist.
Forms part of: Sigmund Freud collection.
Keywords: Psychiatrists